Segregation enabled outstanding combination of mechanical and corrosion properties in a FeCrNi medium entropy alloy manufactured by selective laser melting. (10th February 2022) - Duan, Heng; Liu, Bin; Fu, Ao; He, Junyang; Yang, Tao; Liu, C.T.; Liu, Yong
Highlights: A face-centered cubic single-phase FeCrNi medium entropy alloy with a high Cr ( 35 at.%) content was successfully manufactured by selective laser melting (SLM). This as-SLMed MEA presents a hierarchical microstructure of coarse columnar grains and submicron cell structures. Cr, and also interstitial C, are found segregated to the cell boundaries. The as-SLMed FeCrNi MEA shows a good combination of strength (σ0.2 = 745 MPa, σUTS=1007 MPa) and ductility (εf=31%), as well as a superb corrosion resistance ( i corr =0.06 μA/cm 2 ). Abstract: Selective laser melting (SLM) has the advantage in preparing supersaturated solid solutions due to its unique thermal field and high solidification rate. In this study, a face-centered cubic single-phase FeCrNi medium entropy alloy (MEA) with an ultrahigh Cr content ( 35 at.%) was additively manufactured by SLM. The as-built MEA shows a hierarchical microstructure of coarse columnar grains and submicron dislocation cell structures, where the cell boundaries are probed segregated with Cr and C and decorated with nano carbides. The appearance of these dislocation barriers results in an excellent combination of strength ( σ 0.2 =745 MPa, σ UTS =1007 MPa) and ductility ( ε f =31%). The current MEA also shows a superb corrosion resistance with a corrosion current density of 0.06 μA cm −2 in 3.5 wt.% NaCl solution, which is far lower than that of 316 L. The high content of solutioned Cr in the MEA ensures sufficient Cr supply to form an integrated Cr2 O3 passive film, and the large number of cell boundaries acting as the diffusion channels lead to the fast formation of a stable passive film over the alloy surface. Graphical abstract: Image, graphical abstract